Effect of anti-obesity agent HSG4112 on overweight and obese patients following 12 weeks of oral treatment: a study protocol for a randomised, double-blind, placebo-controlled, parallel-group, phase 2a clinical trial - Min, Kyungha; Oh, Bumjo; Koo, Hye Yeon; Kim, Yang-Hyun; Lee, Ji-Won; Lee, Sangsub; Kim, Youngah; Kwon, Hyuktae (Frontiers in Pharmacology, 2023)
Introduction: HSG4112, a structural analogue of glabridin, acts as a novel anti-obesity mechanism. In subsequent animal and phase one human body experiments, HSG4112 was confirmed to improve energy consumption, normalise weight and obesity, and be safe and resistant to drugs. This led to the manufacturer (Glaceum Inc.) conducting a phase 2a clinical trial to determine the safety and efficacy of HSG4112 in overweight and obese patients. Methods and Analysis: This study will be a randomised, double-blind, placebo-controlled, parallel-group trial that will be conducted for 16 weeks (intervention for 12 weeks) at five large hospitals in South Korea. Those participants deemed eligible to participate in this study based on the inclusion/exclusion criteria will be assigned a subject number and randomly assigned to one of the four treatment groups (one group receiving placebo) in a 1:1:1:1 ratio. The primary outcome of the study will be the change in body weight (kg) from baseline to the end of treatment and the evaluation of safety and tolerability. Discussion: This trial will reveal the efficacy and safety of HSG4112 in overweight and obese adults. If the newly developed mechanism is safe and effective, a significant reduction is anticipated regarding the limitations in the perception of medical personnel and obese patients when choosing to take oral drugs along with the transition to chronic conditions that require long-term management. Trial registration: ClinicalTrials.gov Identifier: NCT05197556, Registered on January 19, 2022 (https://clinicaltrials.gov/ct2/show/NCT05197556). Keywords: Obesity, Overweight, weight loss, obesity drug, randomised controlled trial